Fault tolerant GPS-AOA-SINS integrated navigation algorithm based on federated Kalman filter - Rui JIANG; Jun LI; Youyun XU; Xiaoming WANG; Dapeng LI (Tongxin xuebao)
At present, global positioning system (GPS) was widely used in outdoor positioning.However, the continuous development of cities complicated the positioning environment, resulting in a sharp decline in positioning accuracy.Therefore, the integrated positioning scheme of GPS/5G base station angle of arrival positioning/strap-down inertial navigation system (GPS-AOA-SINS) was adopted, and a fault-tolerant integrated navigation algorithm based on federated Kalman filter was proposed.Based on the GPS-AOA-SINS integrated positioning scheme, the algorithm added fault detection between the federated Kalman sub filter and the main filter, and adaptively adjusted the filter gain matrix of the fault sub filter.Experiments show that the proposed algorithm can effectively detect system faults and deal with them in real time, so as to improve the reliability of the system.